"f(x,y,z,p,q)=p^2+q^2-2px-2qy+1=0"
"\\frac{dp}{p}=\\frac{dq}{q}=\\frac{dz}{p(p-x)+q(q-y)}=\\frac{dx}{p-x}=\\frac{dy}{q-y}"
"\\frac{dp}{p}=\\frac{dq}{q} \\Rightarrow \\ln p=\\ln q + \\ln c \\Rightarrow p=cq"
"q=\\frac{2(cx+y) \\pm \\sqrt{4(cx+y)^2-4(c^2+1)}}{2(c^2+1)}"
"cx+y=t, \\,\\, c^2+1=a"
"dz=pdx+qdy=cqdx+qdy=q(cdx+dy)=qd(cx+y)=qdt""z=\\int \\frac{t \\pm \\sqrt{t^2-a}}{a} \\, dt=\\frac{t^2}{2a} \\pm \\frac{1}{a} \\int \\sqrt{t^2-a} \\, dt"
"z=\\frac{t^2}{2a} \\pm \\frac{1}{2} t \\sqrt{t^2-a} \\mp \\frac{1}{2} a \\ln (\\sqrt{t^2-a}+t)+C"
Comments
Leave a comment